Estresse percebido e duração do sono em universitários trabalhadores - Garbin, Karina (2021)
University education is present in many people's lives, thus making up a stage of the life cycle. A significant number of college students need to balance their academic routine with their workday. It can negatively affect their general health, besides interfering in several other educational and socio -cultural activities. Sleep occupies about one-third of the total human lifespan and is crucial for physical, emotional, and cognitive well -being. Sleep deprivation and its poor quality are posed as a response to stress. This dissertation aims to analyze the relationship between sleep duration and quality with stress levels in working college students. Specifically, it seeks to identify the characteristics of working college students regarding their daily work, study, and leisure hours and analyze the prevalence of perceived stress and its relationship to self -perception of health in this population. The study covers a sample of 406 students fro m Brazilian higher education institutions who conciliate attendance in higher education and working hours. The dissemination of the research took place through social networks. Data was collected using an online questionnaire, which brought together sociodemographic questions, health perception, sleep quality through the Munich Chronotype Questionnaire. Furthermore, perceived stress was managed with the Perceived Stress Scale (PSS-14). The dissertation is part of the research line Biopsychosocial aspects of human aging and presents the first scientific production, entitled "Association between perceived stress and duration of sleep for working college students," which aimed to identify the relationship between perceived stress and duration of sleep in workin g college students. The discussions and results demonstrate that the levels of stress, whether low, moderate, or high, directly correlate with the duration of sleep, corroborating evidence from other studies that associate the overload of activities with h igher levels of stress and shorter sleep time.